2006
DOI: 10.1007/s10750-006-0121-4
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of hydrology and nutrient limitation in the Ridge and Slough landscape of the southern Everglades

Abstract: Extensive portions of the southern Everglades are characterized by series of elongated, raised peat ridges and tree islands oriented parallel to the predominant flow direction, separated by intervening sloughs. Tall herbs or woody species are associated with higher elevations and shorter emergent or floating species are associated with lower elevations. The organic soils in this ''Ridge-and-Slough'' landscape have been stable over millennia in many locations, but degrade over decades under altered hydrologic c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
119
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 100 publications
(123 citation statements)
references
References 46 publications
4
119
0
Order By: Relevance
“…Recent research supports the assumption that N and P resource islands play a sink/source role in landscape-scale biogeochemical cycling (e.g. Jayachandran et al 2004;Ross et al 2006;Wetzel et al 2005Wetzel et al , 2009Givnish et al 2008), but the spatial patterns of resource island gradients have not yet been fully described.…”
Section: Sidroxylon Reclinatummentioning
confidence: 85%
See 2 more Smart Citations
“…Recent research supports the assumption that N and P resource islands play a sink/source role in landscape-scale biogeochemical cycling (e.g. Jayachandran et al 2004;Ross et al 2006;Wetzel et al 2005Wetzel et al , 2009Givnish et al 2008), but the spatial patterns of resource island gradients have not yet been fully described.…”
Section: Sidroxylon Reclinatummentioning
confidence: 85%
“…Landscape features within the Ridge and Slough peatlands are arranged parallel to the predominant historical direction of hydrologic flow (Ross et al 2006). Lower slough communities have relatively long hydroperiods, inundated approximately 11 months per year, and are therefore the main conduits for water flow through the Everglades.…”
Section: Study Sitementioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, it has been shown elsewhere that different combinations of processes may generate similar patterns (Eppinga et al, 2009), making inference of a single dominant mechanism challenging. Models of ridge-slough pattern genesis have invoked differential sediment transport Lago et al, 2010), nutrient redistribution (Ross et al, 2006), and biased subsurface flow induced by anisotropic hydraulic conductivity (Cheng et al, 2011) as driving mechanisms. Using a process-based numerical model, Ross et al (2006) showed that differential evapotranspiration rates in higherelevation soils may lead to the concentration of dissolved nutrients (particularly phosphorus), suggesting that this nutrient redistribution, alone or in combination with sediment and nutrient transport, may generate the ridge-slough pattern in the Everglades.…”
Section: Introductionmentioning
confidence: 99%
“…In arid ecosystems, similar patterns are called labyrinths (Rietkerk et al 2002). Peatland maze patterning can be induced by nutrient accumulation under ridges, which is driven by increased evapotranspiration rates by vascular plants (especially shrubs and trees) that grow on these ridges (Rietkerk et al 2004a;Wetzel et al 2005;Ross et al 2006). This structuring mechanism would imply that because of higher evapotranspiration rates, there is a net flow of water and dissolved nutrients toward ridges.…”
Section: Introductionmentioning
confidence: 99%